Measurement of nitrophenols in rain and air by two-dimensional liquid chromatography-chemically active liquid core waveguide spectrometry - Lucksagoon Ganranoo (2018)
We report a novel system to analyze atmospheric nitrophenols (NPs). Rain or air sample extracts (1 mL) are preconcentrated on a narrow bore (2 mm) aliphatic anion exchanger. In the absence of strong retention of NPs exhibited by aromatic ion exchangers, retained NPs are eluted as a plug by injection of 100 μL of 0.1 M Na2SO4 on to a short (2×50 mm) reverse phase C-18 column packed with 2.2 μm particles. The salt plug passes through the C-18 column unretained while the NPs are separated by an ammonium acetate buffered methanol-water eluent, compatible with mass spectrometry (MS). The eluted NPs are measured with a long path Teflon AF-based liquid core waveguide (0.15×1420 mm) illuminated by a 403 nm light emitting diode and detected by a monolithic photodiode-operational amplifier. The waveguide is rendered chemically active by suspending it over concentrated ammonia that permeates into the lumen. The NPs ionize to the yellow anion form (λmax ∼400 nm). The separation of 4-nitrophenol, 2,4-dinitrophenol, 2-methyl-4-nitrophenol, 3-methyl-4-nitrophenol, and 2-nitrophenol (these are the dominant NPs, typically in that order, in both rain and air of Houston and Arlington, TX, confirmed by tandem MS) takes just over 5 min with respective S/N = 3 limits of detection (LODs) of 60, 12, 30, 67, and 23 pg/mL compared to MS/MS LODs of 20, 49, 11, 20, and 210 pg/mL. Illustrative air and rain data are presented. © 2010 American Chemical Society.